Degradation strategy of cyclin D1 in cancer cells and the potential clinical application - Chen, Shuyi; Li, Ling (Frontiers in Oncology, 2022)
Cyclin D1 has been reported to be up-regulated in several solid and hematologic tumors, promoting cancer progression. Thus, decreasing cyclin D1 by degradation could be a promising target strategy for cancer therapy. This mini review summarized the roles of cyclin D1 in tumorigenesis and progression and its degradation strategies. Besides, we proposed an exploration about the degradation of cyclin D1 by FBX4, a F box protein belonging to E3 ligase SKP-CUL-F-box (SCF) complex which mediates substrate ubiquitination, as well as a postulate about the concrete combination mode of FBX4 and cyclin D1. Furthermore, we proposed the possible photodynamic therapy strategy that based on the above concrete combination mode for treating superficial cancer.